Analisis Konsep Keadilan Syed Muhammad Naquib al-Attas Terhadap Krisis Kebenaran di Era Post-truth - Nur, Muhammad; Audy Rizaki (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This research aims to answer how Syed Muhammad Naquib al-Attas's concept of justice can offer solutions to the crisis of truth in the post-truth era. The post-truth phenomenon is characterized by the dominance of hoaxes, misinformation, and manipulation of public emotions, which reflects the loss of intellectual discipline in treating knowledge. Epistemological defects occur when truth is treated on an equal footing with opinions and conjectures, thus giving birth to epistemic injustice. This study uses a qualitative approach through a literature review of al-Attas' works. The analysis shows that the essence of justice according to al-Attas puts everything in its place and can be applied in the realm of knowledge through manners and the placement of knowledge. This perspective shows that efforts to counter hoaxes, misinformation, and information manipulation are not enough with technical verification alone, but require a reconstruction of epistemic consciousness rooted in the Islamic worldview.